Long-term clinical outcomes of transient and persistent no-reflow following percutaneous coronary intervention (PCI): A multicentre Australian registry - Papapostolou, S.; Andrianopoulos, N.; Duffy, S.; Brennan, Angela; Ajani, A.; Clark, D.; Reid, C.; Freeman, M.; Sebastian, M.; Selkrig, L.; Yudi, M.; Noaman, S.; et al. (ELSEVIER SCIENCE INC, 2018)
© 2018 Europa Digital & Publishing. All rights reserved. Aims: The aim of the study was to evaluate long-term outcomes of transient versus persistent no-reflow. Methods and results: A total of 17,547 patients with normal flow post percutaneous coronary intervention (PCI) were compared to 590 patients (3.2%) with transient no-reflow and 144 patients (0.8%) with persistent no-reflow. Long-term all-cause mortality was obtained by linkage with the National Death Index (NDI). No-reflow patients were more likely to have presented with ST-elevation myocardial infarction (STEMI), out-of-hospital cardiac arrest (OHCA) or cardiogenic shock (all p<0.01). Long-term NDI-linked all-cause mortality was highest in patients with persistent no-reflow (31%) followed by transient no-reflow (22%) and normal flow (14%) over a median follow-up of 5.2, 5.5 and 4.5 years, respectively (all p<0.0001). Kaplan-Meier survival estimates demonstrated a graded increase in all-cause mortality from normal flow, to transient to persistent no-reflow (p<0.01), with the highest mortality occurring early (<30 days) in the persistent no-reflow group (p<0.0001). Multivariate Cox proportional hazards modelling identified glomerular filtration rate <30 mL/min, ejection fraction <30%, persistent no-reflow and transient no-reflow as independent predictors of increased hazard for all-cause mortality (all p<0.05). Conclusions: Transient and persistent no-reflow were associated with a stepwise reduction in long-term survival. The presence of even transient no-reflow appears to be an important predictor of adverse long-term outcome.